Por uma cartografia de cenário: ambiente, comunidade escolar e paisagem - Lage, Aline Lima da Silveira (2008)
The present inquiry, of qualitative character, assessed a small segment pertaining to the school community of CIEP 448 Ruy Frazão Soares with the aim of analyzing the insertion of the local landscape for that community when dealing with the environmental theme. To reach that goal the following aspects were studied: i) a brief historical description of the educational process and the debate concerning the environment; ii) a cartography of the landscape the Engenho do Mato, specially the Bairro-Escola CIEP Ruy Frazão Soares (Niterói/RJ), comparing the bibliographical research from the speeches of interviewed individuals; iii) by means of a composed by script of interviews four questions related with the environment, the evaluated insertion of the local landscape in the speeches of the studied school community was evolvoted; iv) from the talks granted to this study, were produced three categories (Paradox, Protagonism and Visibility) of the speech of the school community. Besides the bibliographical research, it was used Speech Analysis as a theoretic guide and the Analysis of Content techniques. Eighteen interviews had been carried out (seventeen with the school community and one with the Parque Estadual da Serra da Tiririca administrator). Eleven questionnaires were distributed to the educators, amounting to a total of 150 answers/speechs for the analysis. It was observed that the respondent pertaining to the school community includes the Landscape when reflecting concerns about the questions that involve the environment and when doing so questions the educational system and even the social actors participation. This research is justified because it seeks to investigate the interface landscape/scholar community/environment and for sketching a research method (cartography) that can be used in the education for the environment, especially in the initial actions carried through the formal education context. Such method focuses the relevance of the critical look on the reality and the construction of a procedure that has also a dynamic character to accompany the movement/relations produced by the actors in the Landscape.